2019
DOI: 10.1051/0004-6361/201936169
|View full text |Cite
|
Sign up to set email alerts
|

A dense, solar metallicity ISM in the z = 4.2 dusty star-forming galaxy SPT 0418−47

Abstract: We present a study of six far-infrared fine structure lines in the z=4.225 lensed dusty star-forming galaxy SPT 0418-47 to probe the physical conditions of its inter stellar medium (ISM). In particular, we report Atacama Pathfinder EXperiment (APEX) detections of the [OI] 145µm and [OIII] 88µm lines and Atacama Compact Array (ACA) detections of the [NII] 122 and 205µm lines. The [OI] 145µm / [CII] 158µm line ratio is ∼5× higher compared to the average of local galaxies. We interpret this as evidence that the I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 88 publications
7
55
0
Order By: Relevance
“…Here we report the presence of a dynamically cold, but highly star-forming, rotating disk in a galaxy at redshift 6 z = 4.2, when the Universe was just 1.4 billion years old. Galaxy SPT-S J041839-4751.9 is strongly gravitationally lensed by a foreground galaxy at z = 0.263, and it is a typical dusty starburst, with global star-forming 7 and dust properties 8 that are in agreement with current numerical simulations 9 and observations 10 . Interferometric imaging at a spatial resolution of about 60 parsecs reveals a ratio of rotational to random motions of 9.7 ± 0.4, which is at least four times larger than that expected from any galaxy evolution model at this epoch [1][2][3][4][5] but similar to the ratios of spiral galaxies in the local Universe 11 .…”
supporting
confidence: 82%
“…Here we report the presence of a dynamically cold, but highly star-forming, rotating disk in a galaxy at redshift 6 z = 4.2, when the Universe was just 1.4 billion years old. Galaxy SPT-S J041839-4751.9 is strongly gravitationally lensed by a foreground galaxy at z = 0.263, and it is a typical dusty starburst, with global star-forming 7 and dust properties 8 that are in agreement with current numerical simulations 9 and observations 10 . Interferometric imaging at a spatial resolution of about 60 parsecs reveals a ratio of rotational to random motions of 9.7 ± 0.4, which is at least four times larger than that expected from any galaxy evolution model at this epoch [1][2][3][4][5] but similar to the ratios of spiral galaxies in the local Universe 11 .…”
supporting
confidence: 82%
“…Our assumption is additionally motivated by recent spectroscopy studies of DSFGs in the HUDF field, for which metallicities consistent with solar are inferred at 1 < z < 3 (Boogaard et al 2019, see also Nagao et al 2012;Kriek et al 2016;De Breuck et al 2019) 2 . We adopt the flexible star-formation historiy (SFH), which is composed of a delayed component with an additional burst.…”
Section: Stellar Componentmentioning
confidence: 92%
“…Observations of [N II] lines are limited at high-redshift, but the number of detections has been increasing. [NII] 122 µm lines are detected in quasars at z = 7.54 (Novak et al 2019) and at z = 6.003 (Li et al 2020), a dusty star-forming galaxy (DSFG) at z = 4.22 (De Breuck et al 2019), and a submillimeter galaxy (SMG) and quasar system at z = 4.69 (Lee et al 2019), whereas Harikane et al (2020) reported three LBGs at z ∼ 6 that are not detected in [N II] 122 µm lines despite detecting them in [C II] and [O III] lines. In another excitation state, [N II] 205 µm lines are detected in galaxies at z = 5-6 (Pavesi et al 2016), SMGs at 3 < z < 6 (Cunningham et al 2020), and z > 4 objects, including quasars and DSFGs (e.g., Decarli et al 2014;De Breuck et al 2019;Novak et al 2019;Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 99%